An unsuspected histopathological finding —concomitant IgA nephropathy in a patient with ANCA-associated vasculitis: a case report and literature review - Tota, Maciej; Donizy, Piotr; Byrska, Martyna; Krajewska, Magdalena; Kusztal, Mariusz (Frontiers in Immunology, 2023)
Although associations of IgA nephropathy (IgAN) and ANCA-associated vasculitis (AAV) have been described, that coexistence occurs scarcely and requires multidisciplinary management. Herein, we discuss a course of treatment introduced in a patient with two exacerbations. Furthermore, alterations in the histopathological images between two kidney biopsies are presented. The applicability of traditional inflammatory markers, e.g. CRP, in monitoring disease severity in AAV and IgAN is limited. Based on our patient and current literature, we suggest ANCA testing in patients with rapidly progressing IgAN for therapeutic and prognostic purposes. As regards the therapy of IgAN associated with AAV, aggressive immunosuppressive regimens with methylprednisolone and cyclophosphamide are recommended. Alternatively, methylprednisolone with rituximab, plasma exchange, mycophenolate mofetil, and intravenous immunoglobulin (IVIG) could be considered.